CFD-optimization algorithm to optimize the energy transport in pultruded polymer composites - Santos,L. S. (2012)
Pultrusion is a composite manufacturing process in which fibers are pulled continuously through a resin bath for resin impregnation before entering into a heated die, where an exothermic cure reaction occurs. The energy needed to provide the cure reaction depends on many aspects such as cure kinetics and pulling speed. Generally, the pultrusion forming is divided in heat zones that can be heated at different temperature levels. The temperature distribution on the die surface can greatly affect material quality and energy cost. In the present work, through a CFD (Computational Fluid Dynamics) algorithm, it was possible to verify that the energy requirements can be reduced by changing the heating configuration of the pultrusion die. For this, an alternative configuration with internal heaters inside the die body was simulated. The heating rate was considered as the objective function. For the optimization study, we used a stochastic algorithm, the so-called particle swarm optimization (PSO) algorithm. The results showed that the energy spent to cure the resin-fiber system can be reduced considerably.